Digitizing the trails; the design of a low-cost wearable camera rig and development of a computer vision tree species detection model - N. W. G. Trump (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This paper presents a novel solution to a reality capture and 3D contextual mapping problem. A wearable camera rig was designed to capture photographic information of existing trails within North Vancouver, British Columbia, Canada. High-resolution video and 360° images were captured for 3D reconstruction models and the creation of an online virtual tour environment. Pathway width of the existing trails was extracted using a linear feature extraction tool to create detailed base map drawings for the client. A computer vision model was trained to detect tree species from images of tree bark. A summary of the stages of the project, lessons learnt from the use of photogrammetric (Structure from Motion) methods, suggested improvements to the computer vision model, and thoughts on the direction of reality capture methods within the infrastructure sector are given.